2019
DOI: 10.1123/jsr.2017-0056
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Fear of Reinjury and Pain Perception in Athletes With First-Time Anterior Cruciate Ligament Reconstructions by Implementing Imagery Training

Abstract: Clinical Scenario: The anterior cruciate ligament is one of the major stabilizing ligaments of the knee joint by preventing anterior translation of the femur in the closed kinetic chain. A ruptured anterior cruciate ligament may require reconstructive surgery for patients who wish to return to physical activity. For the most part, surgeries are successful at repairing the ruptured ligament and restoring ligamentous function; the percentage of athletes that return to a competitive level of physical activity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 11 publications
1
28
0
1
Order By: Relevance
“…Because scientific research needs to be conducted with adequate theoretical support, rarity or novel research areas are relatively weak in terms of the theoretical foundation. Adopting a complex research approach, complementing the breadth of research with quantitative research methods [64,65], and increasing the depth of research with qualitative research [66] can compensate for research methodological or theoretical shortcomings [67].…”
Section: Study Population and Research Settingmentioning
confidence: 99%
“…Because scientific research needs to be conducted with adequate theoretical support, rarity or novel research areas are relatively weak in terms of the theoretical foundation. Adopting a complex research approach, complementing the breadth of research with quantitative research methods [64,65], and increasing the depth of research with qualitative research [66] can compensate for research methodological or theoretical shortcomings [67].…”
Section: Study Population and Research Settingmentioning
confidence: 99%
“…A previous systematic review by Rodriguez et al [ 18 ] concluded that MI techniques are effective as a psychological intervention, which could reduce post-injury consequences with positive functional and mental outcomes with scarce and no clear evidence. ACL injury has led to numerous different research techniques and therapeutic approaches and has gained an important boom in recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…Fear and pain are the factors that most limit recovery from injuries in athletes, and these factors are quite stressful and frustrating, as well as conditioning physical performance. It would, therefore, be crucial to address these factors during rehabilitation [ 17 , 18 , 19 ]. Physiotherapy and rehabilitation research has not focused on this aspect and the influence on the recovery process [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such engagement can be either real or imagined. Imagery exposure (motor imagery) can potentially reduce the fear of (re)injury and pain in ACLR patients [36].…”
Section: Discussionmentioning
confidence: 99%